Defective dimerization of von Willebrand factor subunits due to a Cys-> Arg mutation in type IID von Willebrand disease. - Schneppenheim, R (1996)
The same heterozygous T -> C transition at nt 8567 of the von Willebrand factor (vWF) transcript was found in two unrelated patients with type III) von Willebrand disease, with no other apparent abnormality. In one family, both alleles were normal in the parents and one sister; thus, the mutation originated de novo in the proposita. The second patient also had asymptomatic parents who, however, were not available for study. The structural consequences of the identified mutation, resulting in the CyS2010 -> Arg substitution, were evaluated by expression of the vWF carboxyl-terminal domain containing residues 1366-2050. Insect cells infected with recombinant baculovirus expressing normal vWF sequence secreted a disulfide linked dimeric molecule with an apparent molecular mass of 150 kDa before reduction, yielding a single band of 80 kDa after disulfide bond reduction. In contrast, cells expressing the mutant fragment secreted a monomeric molecule of apparent molecular mass of 80 kDa, which remained unchanged after reduction. We conclude that CyS2010 is essential for normal dimerization of vWF subunits through disulfide bonding of carboxyl-terminal domains and that a heterozygous mutation in the corresponding codon is responsible for defective multimer formation in type III) von Willebrand disease.